Subsidence of the Corail stem in total hip arthroplasty: no influence of bony contact - Filippo Migliorini; Nicola Maffulli; Marco Pilone; Daniel Kämmer; Ulf Krister Hofmann; Andrea Nobili; Erlis Velaj; Andreas Bell (Journal of Orthopaedics and Traumatology)
Abstract Introduction This study investigated stem subsidence following primary total hip arthroplasty (THA) with a Corail stem in patients who underwent two-staged bilateral THA. The second outcome of interest was to investigate whether a specific single cortical bone contact point might reduce postoperative stem subsidence. Methods The present study was conducted following the STROBE guidelines. The records of patients who underwent THA between 2016 and 2023 were accessed. All patients who underwent two-staged bilateral THA were retrieved. The direct contact between the stem and the cortical bone was assessed at various points in the metaphysis and the distal portion of the stem (diaphysis) in both anteroposterior radiographs of the pelvis (medial and lateral bone contact) and a Lauenstein view of the hip (anterior and posterior bone contact). The following parameters were measured and compared to assess stem subsidence: distance from the proximal femur at the stem bone interface and the tip of the lesser trochanter (distance A); distance from the tip of the lesser trochanter and the tip of the femoral stem (distance B). Results In total, 250 patients were included, 45% (149 of 250 patients) were women and 61% (153 of 250 THAs) were implanted primarily on the right side. The mean age of patients at the time of the first THA was 64.3 ± 10.0 years and the mean body mass index (BMI) was 28.0 ± 4.9 kg/m2. The mean length of the follow-up was 14.1 ± 10.8 months. The overall stem subsidence following THA was 2.8 ± 0.7 mm (P < 0.006). A direct cortical bone-implant contact did not exert a statistically significant difference in subsidence of the THA stem at the metaphysis and diaphysis (P > 0.5). Stem subsidence following THA with a collarless cementless Corail stem was approximately 2.8 mm at 14 months. Conclusions Direct cortical bone contact of the stem at diaphysis and metaphysis seems not to influence stem subsidence following THA using the Corail stem.